Cytoplasmic inclusions in Giardia: An electron microscopy study - Sogayar, M. I.L.; Gregorio, E. A. (Taylor & Francis, 1986)
Ultrastructural observations of Giardia trophozoites showed two different types of cytoplasmic inclusions. In Giardia muris from hamsters, the inclusions scattered in the cytoplasm were round, about 0.2 μm in diameter, limited by a double membrane, and with some electron-dense contents. In G. duodenalis from domestic rats, the inclusions were polyhedral, about 0.2 μm in diameter, limited by a double membrane, and with less electron dense contents. These inclusions have an unknown nature, and evidences show interaction between the inclusions and the Giardia trophozoites.